Strategi Peningkatan Pengelolaan Permukiman Adat Bawomataluo untuk Memenuhi Persyaratan Warisan Dunia - Nurdiana, Mayca Sita (Department of Archaeology, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
Bawomataluo is one of the sites in Indonesia with the potential to become a world heritage. The site is a traditional settlement located in Bawomataluo Village, Fanayama District, South Nias Regency. Bawomataluo Traditional Settlement has been included in the UNESCO tentative list of world heritage since October 6, 2009. However, until now its position is still on the tentative list. This is due to the absence of nomination documents and adequate management. This paper aims to identify efforts that can be made to improve the site’s management. The method used is a literature study and qualitative analysis of various sources including online news articles, scientific articles, government regulations, and normative directives from UNESCO related to world heritage nominations. Management improvement efforts that can be made to support the nomination of Bawomataluo to become a world heritage include stakeholder mapping, community involvement in management efforts, conservation implementation, preservation of traditions or intangible cultural heritage, sustainable tourism development, and preparation of management plan documents. === Bawomataluo merupakan salah satu situs di Indonesia yang berpotensi untuk menjadi warisan dunia. Situs ini merupakan permukiman tradisional yang terletak di Desa Bawomataluo, Kecamatan Fanayama, Kabupaten Nias Selatan. Permukiman Adat Bawomataluo telah masuk ke dalam daftar sementara warisan dunia UNESCO sejak 6 Oktober 2009. Namun hingga saat ini posisinya masih tetap dalam daftar sementara. Hal tersebut dikarenakan belum adanya dokumen nominasi dan pengelolaan yang memadai. Tulisan ini bertujuan untuk mengidentifikasi upaya-upaya yang dapat dilakukan untuk meningkatkan pengelolaan situs tersebut. Metode yang digunakan adalah studi pustaka dan analisis kualitatif dari berbagai sumber meliputi artikel berita online, artikel ilmiah, peraturan pemerintah, dan arahan normatif dari UNESCO terkait pengusulan warisan dunia. Upaya peningkatan pengelolaan yang dapat dilakukan untuk mendukung pengusulan Bawomataluo menjadi warisan dunia meliputi pemetaan stakehoder, pelibatan masyarakat dalam upaya pengelolaan, pelaksanaan konservasi, pelestarian tradisi atau warisan budaya intangible, pengembangan pariwisata berkelanjutan, serta penyusunan dokumen rencana pengelolaan.